The CV as an Initiative for Sustainable Development of Small-Scale Capture Fisheries in Central Java, Indonesia - Mahmudah, Siti; Susilowati, Etty; Soemarmi, Yunanto, Amiek; Badriyah, Siti Malikhatun; Benuf, Kornelius (International Journal of Criminology and Sociology, 2021)
The problem of this study is that small-scale capture fisheries business in Indonesia still faces a classic problem, namely limited sources of capital to develop the business, so a strategy is needed to overcome this problem, including working with other parties as partners in running the business. This study aims to investigate the legality of the capture fisheries business in Indonesia, and the limited partnership (Commanditaire Vennootschap/CV) as an alternative form of capture fisheries business in Indonesia. This study uses a normative juridical research method with a statutory approach and a conceptual approach, the legal data used is secondary data in the form of primary legal materials, namely the Law on Capture Fisheries and the Law on CV, and secondary legal material in the form of literature related to the research problem. The data and legal materials were collected through a literature study and analyzed descriptively and analytically. The results of the study concluded that in carrying out fishery business activities, the entrepreneurs can use CV as an alternative form of small-scale capture fisheries business that allows overcoming the problem of limited capital faced by small-scale capture fisheries entrepreneurs in Indonesia. The study concludes that with the formation of CV, there will be two partners in small-scale capture fisheries business, namely complementary allies as the party who manages what is done by fishermen and limited allies are parties who include capital in small-scale capture fisheries businesses.